The Juridical Validity of the Asset Seizure Prohibition for the Indonesia Investment Authority (INA) - Faizal, Muhammad; Santoso, Budi; Dewi, Amelia Sri Kusuma (IJBLE Scientific Publications Community Inc., 2025)
Article 160, paragraph (3) of the Job Creation Law prohibits the confiscation of assets by the Indonesia Investment Authority (INA). The provision prohibiting asset confiscation raises problems in the form of norm conflicts with the provisions of bail confiscation, criminal confiscation, and bankruptcy confiscation. Therefore, it is necessary to analyze the validity of the norms prohibiting the confiscation of INA assets. Based on this background, the purpose of this study is to analyze the juridical validity of the norms prohibiting the seizure of INA assets. This research uses a statutory and conceptual approach. The type of legal material consists of primary and secondary legal materials sourced from both primary and secondary data. The legal materials are analyzed through interpretation techniques. The results of this study reveal that the norm prohibiting the confiscation of INA assets in positive law does not fulfill the principle of juridical validity, making it an invalid norm. Suggestions to the legislators to make changes to the formulation of Article 160 paragraph (3) of the Job Creation Law in order to fulfill the principle of juridical validity.